Numerical study and optimization of a digital temperature sensor using an Arduino assembly and data modeling with Python. - BENMOUSSA AHMED; KHELLOUFI HADJ AISSA; A. MOUHOUB (Université Amar Thelidji- Laghouat FACULTE: DE TECHNOLOGIE DÉPARTEMENT D'ÉLECTRONIQUE, 2024)
This study explores the implementation and utilization of Arduino, an open-source electronics platform, alongside the Firmata communication protocol. Provides a thorough examination of temperature measurement, elucidating the underlying principles and distinct temperature scales. It also presents sensors such as thermistors and the LM35 temperature sensor, highlighting their use in diverse applications. Explores the Arduino platform, focusing on its hardware and software components, adaptability, and the support it receives from the community. This text explores the importance of the Firmata protocol in enabling communication between microcontrollers and host computers. The text specifically highlights the use of the simpler Firmata Express version, specifically designed for educational and prototyping purposes. The practical implementation of Arduino and Firmata is illustrated by the measurement of temperature using sensors such the LM35. The guide provides comprehensive instructions for configuring the hardware and coding the Arduino using Python and the pyFirmata module. This research highlights the efficacy of Arduino and Firmata in developing adaptable and efficient solutions for diverse electronic tasks.
Dissertation Master Degree in Instrumentation